Mareas rojas provocadas por el dinoflagelado Gymnodinim catenatum (Gymnodiniales: Gyminodiniaceae) en la bahía de Mazatlán, Sin., México, en 1997 - Ramírez-Camarena, Casimiro; Cortés-Altamirano, Roberto; Muñoz-Cabrera, Lucio (Revista de Biología Tropical, 1999)
A total of 31 phytoplankton samples collected during January-December 1997 from Mazatlán Bay, Sinaloa, Mexico, were analized in order to study the red tide dynamics caused by the dinoflagellate Gymnodinium catenutum as well as determining the degree of toxicity thal it could transmit to local oyster products, Phytoplankton samples were quantified using the Uttermohl method, The toxicological analysis were made on oysters (Ostrea iridescens) to detect the PSP (Paralytic Shelfish Poisoning) toxin, by mouse bioassay method. The results showed cases of red tide caused by G. catenatum in April and Oktober, with cell concentralions of 5 000 and 3 873 cells ml-1, respectively. This was the dominant species in the phytoplanklon community with a relative abundance of 99 %. The PSP toxin concentrations were lower than 35 µg 100g-1, which were within the maximum permissible limit (80 µg 100g-1) to avoid health risksin shellfish consumption. The low toxin concentration in oysters compared with a high cell density, could be due to the fact that the denser spots of red tides were far from the oysters beds. This study provides the first. G. catenatum toxin concentration report in Mazatlán Bay.